1795 N.H. Laws 525 - (:unkn) unknown (My University, 1795)
An Act in Addition to an Act, Entitled, "An Act for Regulating the Militia within this State.": [E]very free, able bodied, white male citizen of this state, resident therein, who is, or shall be of the age of sixteen years and under forty years of age, under such exceptions as are made in said act, shall be enrolled in the militia, and shall in all other respects be considered as liable to do the duties of the militia in the same way and manner, as those of the age of eighteen years and upwards. Also prohibited the discharge of firearms by non-officers or private soldiers
Keywords: ARMED FORCES; DISCHARGE